Systemic inhibition and liver‐specific over‐expression of PAI‐1 failed to improve survival in all‐inclusive populations or homogenous cohorts of CLP mice. (June 2014) - Raeven, P.; Drechsler, S.; Weixelbaumer, K. M.; Bastelica, D.; Peiretti, F.; Klotz, A.; Jafarmadar, M.; Redl, H.; Bahrami, S.; Alessi, M. C.; Declerck, P. J.; Osuchowski, M. F.
Summary Background The role of plasminogen activator inhibitor type‐1 (PAI‐1) in abdominal sepsis remains elusive. Objectives To study the influence of inhibition and over‐expression of PAI‐1 upon survival in cecal ligation and puncture (CLP) sepsis. Methods (i) Mice underwent moderate CLP and received 10 mg kg−1 of either monoclonal anti‐PAI‐1 (MA‐MP6H6) or control (MA‐Control) antibody intravenously at 0, 18 or 30 h post‐CLP. The 30‐h treatment group was additionally stratified into mice predicted to survive (P‐SUR) or die (P‐DIE) based on IL 6 measured at 24 h post‐CLP. (ii) PAI‐1 expression was induced with pLIVE.PAI‐1 plasmid administered 72 h pre‐CLP. Blood was sampled for 5 days and survival was monitored for 28 days. Results MA‐MP6H6 effectively neutralized active PAI‐1 and fully restored fibrinolysis while PAI‐1 over‐expression was liver‐specific and correlated with PAI‐1 increase in the blood. Without stratification, MA‐MP6H6 co‐/post‐treatment conferred no survival benefit. Prospective stratification (IL‐6 cut‐off: 14 ng mL−1) suggested increased mortality by MA‐MP6H6 treatment in P‐SUR that reached 30% difference (vs. MA‐Control; P < 0.05) after a retrospective cut‐off readjustment to 3.3 ng mL−1 for better P‐SUR homogeneity. Subsequent prospective anti‐PAI‐1 treatment in P‐SUR mice with 3.3 ng mL−1 cut‐off demonstrated a negative but statistically insignificant effect: mortality was higher by 17% after MA‐MP6H6 vs. MA‐Control. Over‐expression of PAI 1 did not alter post‐CLP survival. Neither PAI‐1 inhibition nor over‐expression meaningfully modified inflammatory response and/or organ function. Conclusions Restoration of fibrinolysis in early abdominal sepsis was not beneficial and it may prove detrimental in subjects with the lowest risk of death, while preemptive PAI‐1 up‐regulation at the current magnitude was not protective.